Classical Scrapie Did Not Re-occur in Goats After Cleaning and Disinfection of the Farm Premises - Konold, Timm; Libbey, Sonja; Rajanayagam, Brenda; Fothergill, Louise; Spiropoulos, John; Vidaña, Beatriz; Alarcon, Pablo (Frontiers in Veterinary Science, 2020)
After an outbreak of classical scrapie in a dairy goat herd with over 1800 goats, all goats in the herd were culled in 2008, cleaning and disinfection of the premises was implemented, and restocking with goats took place approximately 4 months after depopulation. Ten years later the new herd population is over 3000 goats. This study was carried out to determine whether the measures were effective to prevent re-occurrence of scrapie to the 1% prevalence level seen when scrapie was first detected on this farm. A total of 280 goats with a minimum age of 18 months, which were predominantly at the end of their productive life, were euthanized, and brain and retropharyngeal lymph node examined by immunohistochemistry for disease-associated prion protein. Genotyping was done in all euthanized goats and live male goats used or intended for breeding to determine prion protein gene polymorphisms associated with resistance to classical scrapie. None of the goats presented with disease-associated prion protein in the examined tissues, and 34 (12.2%) carried the K222 allele associated with resistance. This allele was also found in four breeding male goats. The study results suggested that classical scrapie was not re-introduced on this goat farm through mass restocking or inadequate cleaning and disinfection procedures. Further scrapie surveillance of goats on this farm is desirable to confirm absence of disease. Breeding with male goats carrying the K222 allele should be encouraged to increase the scrapie-resistant population.